The Learning Style Inventory: Still Less than Meets the Eye - Stumpf, Stephen A.; Freedman, Richard (Academy of Management Review, 1981)
Kolb's reply to our critique of his learning style theory and Learning Style Inventory (LSI) inappropriately overgeneralizes our criticisms of the LSI to all experiential learning theories, excuses low reliability estimates as part of his theory, depends largely on unpublished studies to support his views, and claims strong construct validity support based on unpublished correlations that never exceed -.37. Judged by accepted academic standards, the LSI is an instrument that, if used on an individual learning basis, will result in excessive unreliable and invalid inferences on the part of the user.